Community, Modernity and Peasantry: Philosophical Reflections from a Territorial Conflict - Liceaga, Gabriel (2019)
This article deals with the concept of community in the contemporary Latin American context. Its main purpose is to understand the reactions to this concept and why it is being used frequently as the capitalist modernity processes advance. These thoughts emerge from a research about a specific territorial conflict in Mendoza (Argentina) since 2006. Based on this research, this article analyzes primary sources to consider macro-social processes, which are apprehended through philosophical categories. The main result of this research is an empirically-based analysis of the philosophical dimensions around the community concept, which highlights its utopian projections.